Effluent particle removal by microirrigation system filters - Puig-Bargues, J.=700 1 Arbat, G.; Barragan, J.; Ramirez de Cartagena, F.
(Es, En)
ilus., 24 ref.
Keywords: AGUA; FILTRACION; RIEGO LOCALIZADO; ESPAÑA; OBTURACION